Pencetakan Dokumen melalui Web dan SMS - Chrisdianto, Pang Rendy Arrie; Sevani, Nina (Teknik dan Ilmu Komputer, 2014)
The rapid growth of information technology and telecommunication has speed in many sectors. One of the popular implementation is Short Message Service(SMS) and web. Considering its superiority, we can use SMS tu control access from an application to some devices, like printer. This application was applied by using SMS gateway system. The user as the client will send an SMS command displayed on the computer server connected to the printer. Using this Application will simplify the document printing process as the user can access the printer from remote areas. Literature study was performed to collect the data needed. The design was done by using flowchart and usecase diagram. The testing was done by direct tests to the respondents who already tried the application.ÃÂ Key Word: Printing, Client, Server, SMS Gateway, Web.